Decapoda , Mysidacea, Isipoda, and Tanaidacea from Jørgen Brønlund Fjord, North Greenland, - Just, Jean (Meddelelser om Grønland, 1970)
From Jørgen Brønlund Fjord (82°10’ N, 30°30’ W) 29 species of Crustacea Malacostraca are listed: 2 Decapoda, 3 Mysidacea, 15 Isopoda, and 9 Tanaidacea. Two species are considered new to science, viz. Nannoniscus hanseni and Pseudomesus sp. (nov. sp.). Two genera and 9 species are recorded for the first time from Greenland waters.